Implementasi Penyaluran Bantuan Pupuk Bersubsidi di Desa Sumber Katon Kecamatan Seputih Surabaya Kabupaten Lampung Tengah - Mirnawati, Mirnawati; Widodo, Wahyu; Setioko, Sigit; Widodo, Tri; Salamah, Umi (Tapis: Jurnal Penelitian Ilmiah, 2024)
One of the government policies in agriculture that requires effective implementation is subsidized fertilizer distribution programs which is regulated in the Minister of Trade Number: 15/M DAG/PER/4/2013 which explains the Provision and Distribution of Subsidized Fertilizers for the Agricultural Sector. However, this program was not run well. The purpose of this study is to determine communication, resources, and disposition in the implementation of subsidized fertilizer distribution in Sumber Katon Village, Seputih Surabaya District, Central Lampung Regency. This research uses qualitative methods, while the research sources consist of primary data and secondary data, determining informants, namely purposive sampling techniques or deliberately choosing people who are considered to be able to provide accurate information. The data collecting techniques were observation, interview, and documentation. The research results show that there has been good communication between the government, distributors, and the community distributing subsidized fertilizer based on the results of the Definitive Group Needs Plan. Communication is also established between Distributors, Retailers, and farmers. However, providing information is not optimal, and there was a limiting fertilizer quota. Good implementation of subsidized fertilizer distribution continues to be pursued despite many obstacles.